Deregulation of hsa-miR-20b expression in TNF-α-induced premature senescence of human pulmonary microvascular endothelial cells - Wong, Pooi Fong; Jamal, J.; Tong, K.L.; Khor, E.S.; Yeap, C.E.; Jong, H.L.; Lee, S.T.; Mustafa, Mohd Rais; AbuBakar, Sazaly (Elsevier, 2017)
miRNAs are important regulators of cellular senescence yet the extent of their involvement remains to be investigated. We sought to identify miRNAs that are involved in cytokine-induced premature senescence (CIPS) in endothelial cells. CIPS was established in young human pulmonary microvascular endothelial cells (HMVEC-Ls) following treatment with a sublethal dose (20 ng/ml) of tumor necrosis factor alpha (TNF-α) for 15 days. In parallel, HMVEC-Ls were grown and routinely passaged until the onset of replicative senescence (RS). Differential expression analysis following miRNA microarray profiling revealed an overlapped of eight deregulated miRNAs in both the miRNA profiles of RS and TNF-α-induced premature senescence cells. Amongst the deregulated miRNAs were members of the miR 17–92 cluster which are known regulators of angiogenesis. The role of hsa-miR-20b in TNF-α-induced premature senescence, a paralog member of the miR 17–92 cluster, was further investigated. Biotin-labeled hsa-miR-20b captured the enriched transcripts of retinoblastoma-like 1 (RBL1), indicating that RBL1 is a target of hsa-miR-20b. Knockdown of hsa-miR-20b attenuated premature senescence in the TNF-α-treated HMVEC-Ls as evidenced by increased cell proliferation, increased RBL1 mRNA expression level but decreased protein expression of p16INK4a, a cellular senescence marker. These findings provide an early insight into the role of hsa-miR-20b in endothelial senescence.